WATER-SOLUBLE N -SUBSTITUTED CHITOSAN DERIVATIVES - Ph. Le Dung; D.T. Thien; N.T. Dong; T.T.Y. Nhi; N.T. An (ASEAN Journal on Science and Technology for Development, 2005)
Many water-solubleN-substituted chitosan derivatives have been prepared having the typical -NH-CH2- linkage. Both the Michael reaction and alkylation with monochloroacetic acid at pH 8- 8.5 offer relatively simple ways for their synthesis.